European social policy: Progressive regression - Wolfgang Streeck (Max Planck Institute for the Study of Societies, 2018)
European social policy changed with the evolution of European and global capitalism, the scope and shape of European-level international institutions, the size and heterogeneity of "Europe" as a polity, and the politics of the European national welfare state. The paper outlines the long-term trajectory of European social policy, from the intended absorption of national welfare states into one united, federal welfare state to a selective updating of national social policies by European social policies; to multi-level coordination of national systems by special European institutions; to European soft law helping national "modernization" on the "Third Way"; to exposure of national systems to international economic competition as an incentive for "structural reform"; and to subordination of social policy, national and European, to the defense of a common hard currency through fiscal consolidation - from, in other words, federal social democracy to competitive "adjustment" of national social protection and social life to global markets. – – Die europäische Sozialpolitik entwickelte sich zusammen mit dem Wandel des europäischen und globalen Kapitalismus, der Reichweite und Gestalt europaweiter politischer Institutionen und der Größe und Vielfalt von "Europa" als politisches System sowie der Politik des europäischen Wohlfahrtsstaats auf nationaler Ebene. Der Aufsatz zeichnet die langfristigen Entwicklungslinien der europäischen Sozialpolitik nach, von der beabsichtigten Absorption der nationalen Wohlfahrtsstaaten in einen gemeinsamen, föderalen europäischen Wohlfahrtsstaat; zu selektiver Modernisierung nationaler durch europäische Sozialpolitik; zu Mehrebenenkoordination nationaler sozialpolitischer Regime durch spezialisierte europäische Institutionen; zu europäischem Soft Law zur Unterstützung nationaler "Modernisierung" auf dem "Dritten Weg"; zur Öffnung nationaler Systeme für internationalen wirtschaftlichen Wettbewerb als Anreiz zu "Strukturreformen"; schließlich zur Unterordnung von Sozialpolitik, auf nationaler wie europäischer Ebene, unter die Verteidigung einer gemeinsamen harten Währung durch fiskalische Konsolidierung - von, in anderen Worten, bundestaatlicher Sozialdemokratie zu wettbewerblicher Anpassung nationaler Formen des sozialen Schutzes und des sozialen Lebens an globale Märkte und die von ihnen ausgehenden Zwänge.
hdl:21.11116/0000-0002-AA53-1
Keywords: 300; Europe; European integration; European social policy; Europa; europäische Integration; europäische Sozialpolitik